Analysis of The Basis of The Judge's Considerations in Canceling A Waffelicious Registered Trademark on The Basis of Registration in Bad Faith (Ruling Study Number 5/Pdt.Sus.HKI.Merek/2021/PN Smg) - Yoga Pratama Putra; Tashya Panji Nugraha (Proceeding International Conference Restructuring and Transforming Law, 2023)
This study aims to identify the premise and types of legal protection for trademark rights, to analyze the judge's considerations in making a decision on Waffelicious trademark registration. “This study conducts a comparative analysis of legal literature, focusing on books on Trademark Rights as the primary data source. Data is collected, analyzed, categorized, and aggregated drawn. The results of this study are that trademark law must provide a clear understanding of the interpretation of good faith so that in its application it does not cause differences in interpretation between judges, so that each Supreme Court decision has the consistency of legal certainty that can provide legal protection to trademark owners.”